2019
DOI: 10.3389/fimmu.2019.02493
|View full text |Cite
|
Sign up to set email alerts
|

NKT-Like (CD3+CD56+) Cells in Chronic Myeloid Leukemia Patients Treated With Tyrosine Kinase Inhibitors

Abstract: Therapy with Tyrosine Kinase Inhibitors (TKI) aiming stable deep molecular response is the gold standard to treat Chronic Myeloid Leukemia (CML). NKT-like cells (CD3+CD56+) combine characteristics of T and NK cells. The physiopathological role of these cells remains unknown although the literature refers their association with inflammation, autoimmune diseases, and cancer. Since the information regarding the role of NKT-like cells in CML is rare, we aimed at the characterization of these cells in CML patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 54 publications
0
23
1
Order By: Relevance
“…In terms of immunosuppression in cancer, galectin-9 (Gal-9) is the most important TIM-3 ligand. In CML, increased expression of TIM-3 was detected on NKT cells [ 81 ]. Bruck et al identified increased expression of TIM-3, PD-1 and CTLA-4 on CD4+ and CD8+ T cells in the bone marrow of CML patients, compared with control samples [ 41 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of immunosuppression in cancer, galectin-9 (Gal-9) is the most important TIM-3 ligand. In CML, increased expression of TIM-3 was detected on NKT cells [ 81 ]. Bruck et al identified increased expression of TIM-3, PD-1 and CTLA-4 on CD4+ and CD8+ T cells in the bone marrow of CML patients, compared with control samples [ 41 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%
“…It is suggested that tumor cells express MHC-II to bind with LAG-3 and inhibit TCR signaling on effector T cells. As LAG-3 is overexpressed on T cells in CML and AML patients [ 71 , 81 ], it could be yet another way to evade immune response by leukemic cells [ 98 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%
“…NKT cells are known to share receptors expressed by both T and NK cells ( Lanier, Spits & Phillips, 1992 ). Previous evidence also suggests expression of HLA-DR on NKT cells under certain disease conditions or changes in cytokine milieu ( Saikh, Kissner & Ulrich, 2002 ; Almeida et al, 2019 ), which may play an important role in inflammation and immune regulation ( Marrero, Ware & Kumar, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…NK-like T cells are usually defined as CD3+ CD56+ cells and have also been referred to as CD56(+) T, NKT-like cells, and even NKT in published references. Studies on NK-like T cells in RA are scarce, and related knowledge is limited, controversial, and heterogeneous [58]. Accumulation of CD56 (+) T cells was detected in RA and may be involved in maladaptive immune responses, and these T cells have been suggested as potential targets for therapy [59].…”
Section: Discussionmentioning
confidence: 99%